'Do animals talk in this dimension? 'Cos I don't wanna freak anyone out': Writing for children's animation. (1st September 2021) - Wells, Paul
This article discusses a series of screenwriting for animation workshops dedicated to writing for children, using the specific characteristics of the animated form, and seeking to identify the particularity of creating material for a children's audience. The discussion explores different approaches for children of a variety of ages, cultural backgrounds and national contexts. It takes into account global theories of child welfare and the needs of practitioners in speaking to issues of child development and social and educational sensitivities.